Evaluation of the effect of video tutorial training on improving pharmacy students' knowledge and skills about medication reconciliation - Rana K. Abu Farha; Mays Rashad; Eliza Hasen; Tareq Mukattash; Amna Al-Hashar; Iman A. Basheti (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objectives: This study aimed to describe the effect of using an innovative teaching strategy using a video tutorial on enhancing students' knowledge about medication reconciliation, and skills in identifying medication discrepancies. Methods: This is a one group pre-post interventional study that was conducted at the School of Pharmacy at Applied Science Private University. Sixty pharmacy students were invited to attend an educational sessions that involve watching a 6-minutes video tutorial. The first two levels of the Kirkpatrick's Model were used to evaluate the effectiveness of this training tool. Level 1 (Reaction) was assessed using a satisfaction questionnaire, while level 2 (Learning) was assessed using two criteria: 1) student acquired knowledge about medication reconciliation using a questionnaire and a knowledge score out of 13 was calculated for each student, and 2) student acquired skills in identifying medication discrepancies using a virtual case scenario. If the student was able to identify any of the four impeded discrepancies he/she rewarded 1 point for each identified discrepancy, but if they identified any incorrect discrepancy they scored a negative point. Results: Among the 60 students who registered to participate in the study, 49 attended the educational training (response rate 81.6%). The majority of them (n=44, 89.8%) were satisfied with the training process. Before the video tutorial, students showed an overall low knowledge score [4.08/13.0, SD 1.81], and low ability to identify discrepancies [0.72 identified discrepancies out of 4.0, SD 1.1]. Following the video tutorial, the overall knowledge score was improved (p<0.001), and students were able to identify more discrepancies after watching the video (p<0.001). Conclusion: In conclusion, video education has shown itself to be an effective method to educate pharmacy students.. This visualized method can be applied to other areas within pharmacy education. We encourage the integration of videos within the learning process to enhance students' learning experience and to support the traditional learning provided by the teaching staff.